PAMAM Dendrimers as Potential Carriers of Gadolinium Complexes of Iminodiacetic Acid Derivatives for Magnetic Resonance Imaging. (25th February 2015) - Markowicz-Piasecka, Magdalena; Sikora, Joanna; Szymański, Paweł; Kozak, Oliwia; Studniarek, Michał; Mikiciuk-Olasik, Elżbieta
Abstract : This is the first study describing the utilization of PAMAM dendrimers as delivery vehicles of novel magnetic resonance imaging (MRI) contrast agents. The purpose of this paper was to establish the potential of G4 PAMAM dendrimers as carriers of gadolinium complexes of iminodiacetic acid derivatives and determine imaging properties of synthesized compounds in in vivo studies. Furthermore, we examined the influence of four synthesized complexes on the process of clot formation, stabilization, and lysis and on amidolytic activity of thrombin. Biodistribution studies have shown that the compounds composed of PAMAM G4 dendrimers and gadolinium complexes of iminodiacetic acid derivatives increase signal intensity preferably in liver in range of 59–116% in MRI studies which corresponds with the greatest accumulation of gadolinium after administration of the compounds. Synthesized compounds affect kinetic parameters of the proces of clot formation, its stabilization, and lysis. However, only one synthesized compound at concentration 10-fold higher than potential plasma concentrations contributed to the increase of general parameters such as the overall potential of clot formation and lysis (↑CLAUC ) and total time of the process (↑ T ). Results of described studies provide additional insight into delivery properties of PAMAM dendrimers but simultaneously underscore the necessity for further research.